RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN BIT (Beta vulgaris L.) TERHADAP BEBERAPA KONSENTRASI DAN CARA APLIKASI PAKLOBUTRAZOL - Hasibuan, Ainis Sa’idah; Berliana, Yunida; Kurniawan, Dedi; Razali (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2024)
This research was conducted in Medan Marelan District, Medan City, North Sumatra. This research began in April 2024 until July 2024. The aim of this research was to determine the effect of administering several concentrations and methods of application of Paklobutrazol on the growth and production of beet plants. This research used a factorial randomized block design (RAK) consisting of two treatment factors, with the first factor being Paklobutrazol with the symbol (P) consisting of 3 treatment levels, namely: P0 = control, P1 = Paklobutrazol 0.5 grams/plant, P2 = Paclobutrazol 1 gram/plant. The second factor is the application method with the symbol (A) which consists of 2 levels, namely A1 = pour 100 ml of water/plant, A2 = sow. The parameters observed in this research were plant height (cm), number of leaves (strands), wet weight per plant (gr), tuber weight per plant (gr), and sugar content per plant (%). The results of the research showed that Paklobutrazol treatment had a very significant effect on plant height at 6 WAP and 7 WAP, wet weight per plant, tuber weight per plant. The application treatment had a very significant effect only on the tuber weight parameter per plant. The interaction of the two treatments had a very significant effect on plant height at 5 WAP, 6 WAP and 7 WAP, number of leaves at 5 WAP, 6 WAP and 7 WAP, fresh weight of plants, weight of tubers per plant, and sugar content per plant. The best treatment combination was in treatment P1A1 (Paklobutrazol 0.5 grams per plant) and (application method with cocor).